Criminalization of Gratification as a Corruption Offense - Samsul Huda; Bambang Sugiri; Nurini Aprilianda; Heru Ratno Hadi (PT FORMOSA CENDEKIA GLOBAL, 2022)
Gratification or gifts are criminal acts of corruption, if given to state officials or civil servants. The form of corruption is bribery. This corruption crime was only formulated in Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption (hereinafter referred to as the Corruption Law). The birth of the regulation regarding gratification as one of the criminal acts of corruption in the Anti-Corruption Law is a form of state anticipation in dealing with various new modus operandi in acts of corruption. In order to provide a sense of justice, usefulness and legal certainty in its implementation, gratification offenses should be prepared on a philosophical, sociological and juridical basis. The study aims to find out bribe and gratification acts. This study uses normative research methods. Moreover, as part of the element of offense in the criminal act of corruption with the offense itself being the recipient of gratification, the proof in gratification adheres to the principle of the reverse burden of proof. Therefore, in the Law on the Eradication of Criminal Acts of Corruption, Gratification recipients are required to submit a report to the Corruption Eradication Commission (KPK) within 30 (thirty) days. the gratification report is received by the KPK, within 30 (thirty) days the KPK will determine whether the gratification is a bribe or not. If it is proven that a bribe is proven, the gratuity will become the property of the state and vice versa if it is not related, then the gratification becomes the right of the recipient of the gratification